If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 3x + 8 Reorder the terms: 2(-1 + x) = 3x + 8 (-1 * 2 + x * 2) = 3x + 8 (-2 + 2x) = 3x + 8 Reorder the terms: -2 + 2x = 8 + 3x Solving -2 + 2x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 2x + -3x = 8 + 3x + -3x Combine like terms: 2x + -3x = -1x -2 + -1x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + -1x = 8 + 0 -2 + -1x = 8 Add '2' to each side of the equation. -2 + 2 + -1x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 8 + 2 -1x = 8 + 2 Combine like terms: 8 + 2 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 3(6-x)=5 | | 8x+12y^2=0 | | 15s^2+19s+6= | | -9x+2x-8x=0 | | v^2-42=-35v | | n^5+80=5n^4+16n | | 5n-12n=35 | | 8m=4m | | 8(k-4)=4-3k | | 180=x+x+24 | | 2(3+5)-9=a | | 4.6z-7=3.6z-7 | | x^2+4x-4x-16=0 | | 18y^2-21y-9= | | 4(5x-3)+2(15-2x)-5(3x+1)=-3 | | 8x+39=3x+9 | | x*1.66666666667=7.5 | | G(-9)=8*81-11 | | 5t+1+2t-6t=6+4 | | 16+3(4X-3)= | | 3.7x-3.5=x+5.4 | | x^2+11x+20=-4 | | x+1.2=9.3 | | (6x+3)+(-7x+8)= | | m-38=-43 | | 6Y+4-3Y+9= | | 8x+3+5x+9=12x+4 | | 5-2b=3 | | y-42=-32 | | 5x^2+19x+25=7 | | 3(2m+5)form=2 | | 3x^2-8=x^2+28 |